Pljučnica, povzročena s Candido krusei, kot zaplet zdravljenja tubo-ovarijskega abscesa - Uranjek, Jasna (Zdravniški vestnik, 2006)
Background Frequency of infections, caused by Candida glabrata and Candida krusei, which are more resistant to fluconazole, is increasing among hospitalised patients, especially among patients in intensive care units (ICU). Systemic Candida infections are particularly dangerous. Pneumonia, caused by Candida species, most commonly albicans, rarely others, is a seriousinfection especially for immunocompromised patients. It's often fatal. We present a case report of a serious lung infection with fluconazole resistant Candida krusei in a 42 year-old previously healthy patient with perforated tuboovarian abscess (TOA), consecutive severe sepsis and septic shock. Patient used intrauterine device (IUD) for 17 years without any gynaecological controls. Ascending genital infection with E. colli and Streph.chromogenes led to TOA. In spite of empirical antibiotic treatment, surgical and intensive care supportive therapy of affected organs, patient's condition critically deteriorated until exact fungus specification was made and specific antifungal therapy for Candida krusei with voriconazol was started. After that patient's condition improved. Conclusions Connection between patient's age, IUD use duration and severity of the pelvic inflammatory disease (PID) was seen as multiorgan septic dysfunction with dominant lung failure. Candida pneumonia is rare with non-neutropenic patients. Especially with "non albicans" species. We believe Candida krusei infection in ourpatientis related to general weakness and immunocompromised condition because of prolonged and severe PID. Candida krusei infection needs immediate specific antifungal treatment. It was the first Candida krusei infection in our ICU.
Keywords: Adneksitis; Adnexitis; Adult; Adverse Effects; Candida; Candida krusei; infekcijske bolezni; Intrauterine Devices; Intrauterini vložki; Kandida; Odrasli; pelvično vnetje; Pljučnica; Pneumonia; therapy; zdravljenje